1973
DOI: 10.1161/01.cir.48.6.1227
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Obstructive Coronary Disease by Maximal Exercise and Atrial Pacing

Abstract: The reliability of graded maximal exercise treadmill testing and right atrial pacing in diagnosing significant obstructive coronary artery disease was evaluated in 74 consecutive patients referred to a cardiac unit with chest pain consistent with angina pectoris. The results of maximal exercise testing and right atrial pacing, with regard to the presence or absence of the patient's characteristic chest pain or discomfort and ischemic ST segment depression, were compared with the findings determined by selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

1976
1976
1990
1990

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…Fast atrial pacing is a safe procedure to detect coronary insufficiency (Kelemen et al, 1973;Piessens, Van Mieghem, Kesteloot & De Geest, 1974). We cannot state with certainty that our patients do not have coronary heart disease but their normal pacing tests make it unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast atrial pacing is a safe procedure to detect coronary insufficiency (Kelemen et al, 1973;Piessens, Van Mieghem, Kesteloot & De Geest, 1974). We cannot state with certainty that our patients do not have coronary heart disease but their normal pacing tests make it unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…We used acute plasma volume expansion to reveal incipient left ventricular dysfunction (Sanghvi, Khaja, Mark & Parker, 1972;Roche, Masquet, Gourgon, Macrez & Bouvrain, 1974) and atrial pacing to detect coronary artery disease (Linhart, 1972a;Kelemen, Gillilan, Bouchard, Heppner & Warbasse, 1973). (Documenta Geigy, 1963).…”
Section: Introductionmentioning
confidence: 99%
“…Although a mainstay in diagnosing coronary artery disease (CAD), the exercise ECG has a reported false-negative rate of approximately 35% and a false-positive rate of 15% in large populations of symp tomatic patients (Ascoop et al, 1971;Bartel et al. 1974a;Degenais et al, 1977;Goldschlager et al, 1976;Kaplan et al, 1973;Kassebaum et al, 1978;Kelemen et al, 1973;Linhart and Turnoff, 1974;McHenry et al 1972;Martin and McConahay, 1972;Mason et al, 1967;Roitman et al, 1970;Sketch et al. 1975;Vieweg et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…phaseless filter ; heart rate ; ST segment level ; exercise stress test A maximal or submaximal exercise ECG test has been advocated as a reliable method for the early detection of coronary artery disease, but there are still some limitations in the clinical application of these tests. Many reports have shown that about 10 to 19% of patients with ischemic heart disease revealed significant ST segment level changes only during exercise (Bellet et al 1961;McConahay et al 1971;McHenry et al 1972; Kehleman et al 1973;Froelicher et al 1974). These reports have suggested that ECG recording during exercise is required for accurate diagnosis.…”
mentioning
confidence: 99%